California Elected Women's Association for Education and Research membership letter - Sue Hone:::::: (1977)
This July 26, 1977 letter from CEWAER President Sue Hone invites members to attend a Governor's Conference for California Elected Women on August 10, 1977, called by Governor Jerry Brown. The day's program includes discussions with the Governor and senior staff, legislative leaders from both parties, and Chief Justice Rose Bird, followed by an optional dinner with women legislators. Attendance is limited to fifty participants, with registration handled on a first-come basis.